2009
DOI: 10.1289/ehp.0800023
|View full text |Cite
|
Sign up to set email alerts
|

Association of Traffic-Related Air Pollution with Children’s Neurobehavioral Functions in Quanzhou, China

Abstract: BackgroundWith the increase of motor vehicles, ambient air pollution related to traffic exhaust has become an important environmental issue in China. Because of their fast growth and development, children are more susceptible to ambient air pollution exposure. Many chemicals from traffic exhaust, such as carbon monoxide, nitrogen dioxide, and lead, have been reported to show adverse effects on neurobehavioral functions. Several studies in China have suggested that traffic exhaust might affect neurobehavioral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(112 citation statements)
references
References 21 publications
2
110
0
Order By: Relevance
“…Researchers have shown that children exposed to air pollution perform worse on cognitive functioning tests 6 and have impaired neurological function [7][8][9] and lower IQ scores 10 compared with other children. Also, children exposed to high levels of nitrogen dioxide-a common air pollutant generated by the burning of fossil fuels-have been found to have "decreases of 6.71, 7.37 and 8.61 points in quantitative, working memory and gross motor areas, respectively."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that children exposed to air pollution perform worse on cognitive functioning tests 6 and have impaired neurological function [7][8][9] and lower IQ scores 10 compared with other children. Also, children exposed to high levels of nitrogen dioxide-a common air pollutant generated by the burning of fossil fuels-have been found to have "decreases of 6.71, 7.37 and 8.61 points in quantitative, working memory and gross motor areas, respectively."…”
mentioning
confidence: 99%
“…11 Similarly, children with high levels of exposure to nitrogen dioxide and particles 10 micrometers or less in the air-a standard used by the Environmental Protection Agency (EPA) to measure air quality-perform significantly worse on neurobehavioral tests, even after confounding variables are controlled for. 6 In one example of this kind of test, to measure line discrimination, the subject is instructed to hit the space bar on a computer keyboard within a second after seeing a long line, when being presented with long and short lines. And children with high levels of estimated exposure to black carbon-tiny particles released into the air by diesel exhaust, for example-have a decreased ability to perform well on both verbal and nonverbal intelligence and memory assessments, such as the Kaufman Brief Intelligence Test and the Wide Range Assessment of Memory and Learning.…”
mentioning
confidence: 99%
“…Black carbon exposure caused downgrading of IQs in babies at 9 year age [175]. Significant reduction in psychomotor, attention and sensory scales, without cognitive impairment was observed in children studying at school located in area of dense city traffick, compared to those from clean air area [176].…”
Section: Studies On Disruptive Exposurementioning
confidence: 96%
“…In 2005 we conducted a cross-sectional study and found that after controlling the potential confounding factors uusing ordinal logistic regression analysis, participants living in the polluted area showed poor performance on visual simple reaction time, continuous performance, digit symbol, pursuit aiming, and sign register [11]. Although these results were important to understand the associations between TRAP exposure and neurobehavioral disorders, while domain-specific neurobehavioral effects could not be identified because every test directly or indirectly assesses more than one domain of neurobehavioral function.…”
Section: Associations Of Traffic-related Airmentioning
confidence: 99%